PROFESIONALISME PEGAWAI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN DALAM PENANGGULANGAN KEBAKARAN PEMUKIMAN DI KABUPATEN INDRAGIRI HILIR - Ella Sri Ningsih; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indragiri Hilir Regency is a district that has a population density and is at risk of having a disaster, one of which is fire. The Fire and Rescue Service needs to prepare elements that are essential in fire disaster management so that fire events do not occur repeatedly. The purpose of this study was to determine the professionalism of the Fire and Rescue Service staff in dealing with residential fires in Indragiri Hilir Regency and to determine the inhibiting factors for the professionalism of the Fire and Rescue Service staff in handling residential fires in Indragiri Hilir Regency. This study uses 4 (four) indicators of professionalism by Sedarmayanti (2010: 96) which consist of competence, effectiveness, efficiency and responsibility. This type of research is qualitative research with a descriptive approach. The collection of data obtained both primary data and secondary data were collected through interviews, observation and documentation then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the professionalism of fire and rescue employees in residential fire management has not been implemented optimally, this is due to several inhibiting factors, namely facilities and infrastructure, environmental factors and geographical factors. Observation and documentation are then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the professionalism of fire and rescue employees in residential fire management has not been implemented optimally, this is due to several inhibiting factors, namely facilities and infrastructure, environmental factors and geographical factors. observation and documentation are then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the professionalism of fire and rescue employees in residential fire management has not been implemented optimally, this is due to several inhibiting factors, namely facilities and infrastructure, environmental factors and geographical factors. Keywords: Profesionalism, Countermeasures, Fire.